Study of Low Temperature Sintering Glass-Ceramic Using Fly Ash - Ren, Qifang; Ding, Yi; Zhu, Shaofeng; Hu, Puhua (Asian Journal of Chemistry, 2012)
By using orthogonal test, flexure strength and volume density as mostly performance index, by means of SEM and XRD, the glass-ceramic of the sintering and crystallization are investigated. The optimal parameters for the heat treatment of the glass is that the glass should be heated to 770 ºC, holding for 1h, then heated to 875 ºC, holding for 3 h. The crystallization temperature is the most important to the mechanical property of the glass-ceramics and holding time for nucleation is least. The main crystal phase is wollastonite by JSPDC cards and the crystal morphology of No. 4 is complete by SEM.